The influence of employee fit dimensions on job satisfaction, organisational citizenship behaviour and intention to stay in selected South African municipalities - Masoka, Josiah Coba (Vaal University of Technology, 2021)
Given the inevitable changes and dynamics in the nature of the global market, the recruitment, attraction, employment, motivation and retention of valuable workers has become critical for the continued success of both employees and organisations. Organisations are continuously faced with the dilemma of uncovering and understanding employment packages that are essential in attracting fitting individuals to join their establishment and remain in such organisations for a longer period of time. Similarly, people spend a substantial amount of effort and time searching for organisations and jobs that matches their qualifications and skills; fulfil their specific needs, while meeting their goals and values. This study investigated the influence employee fit dimensions (person-job fit, person-environment fit and person-organisation fit) on job satisfaction, organisational citizenship behaviour and intention to stay. These different conceptualisations of fit have typically been studied independently, but this study responded to calls that proposed for a study that incorporated multiple types of employee fit dimensions in a single study. When deliberating on the different fit concepts, some empirical evidence confirmed the existing conceptual distinctions between the three types of fit such as person-job fit, person-environment fit, and person-organisation fit and how each fit dimension positively or negatively influences job satisfaction and the extent to which job satisfaction influences organisational citizenship behaviour. Furthermore, the study examined the influence of organisational citizenship dimension on intention to stay. This study is embedded in a post-positivist quantitative research paradigm. The positivism paradigm was adopted as its underlying philosophy is grounded on cause-effect relationships amongst constructs within a given theoretical model. Since the study was descriptive in nature, the reliability and validity of data was analysed and correlation analysis and regression analysis were also computed. The exploratory factor analysis was performed using the Kaiser-Meyer-Olkin test and the Bartlett’s test of sphericity in order to examine the appropriateness of data for factor analysis and to establish the interrelationship amongst constructs. Preceding the main study’s data collection process, a pilot survey was undertaken to examine the correctness and accuracy of the questionnaire. The data collected were examined with the use of the Statistical Package for the Social Sciences (SPSS) 25.0. The KMO values of all the constructs were above 0.80 which is well within the acceptable value of 0.50. Normality tests were performed using the skewness and kurtosis values and the standard deviation values ranged from 0.65311 to 1.05471 indicating that data was normally distributed. To confirm the consistency of the measuring instrument and its items, reliability tests were carried out and the results indicated that all the constructs were within range (0.786 to 0.891), having surpassed the threshold for reliability of 0.70. The results of the consistency of measures demonstrated that the measuring instrument was reliable. The correlation analysis revealed that there is a strong relationship between person-job fit, person-environment fit, person-organisation fit and job satisfaction. The results further disclosed a moderate association between job satisfaction with altruism, courtesy and civic virtue. A negative relationship is reported between job satisfactions and sportsmanship. A weak but positive relationship is shown between job satisfaction and conscientiousness. The results further indicate a moderate relationship between altruism, conscientiousness and intention to stay. The relationship between courtesy, sportsmanship and intention to stay is reportedly weak. The results indicate that a positive relationship exists between civic virtue and intention to stay. Regression analysis was also performed in order to establish the predictive relationships between variables. The regression analysis results indicate that person-job fit, person-environment fit and person-organisation fit are positive predictors of job satisfaction. Further, altruism, courtesy, civic virtue and conscientiousness contributed positively towards predicting job satisfaction. The results further reveal that sportsmanship showed no relationship with job satisfaction and weak predictor of job satisfaction. The results of the regression analysis further revealed that altruism, courtesy, civic virtue and conscientiousness showed no predictive relationship with intention to stay. However, sportsmanship showed strong predictive relationship towards intention to stay. The study proposes both the theoretical and practical contributions to the organisational behaviour and human resource management literature in the form of recommendations. Limitations and implications for further research is alluded to. The outcome of this study advanced a framework of the influence of employee fit dimensions on job satisfaction, organisational citizenship behaviour and intention to stay which may possibly benefit future researchers.
Ph. D. (Business Administration, Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Influence employee fit dimensions; Job satisfaction; Organisational citizenship behaviour; Human resource management literature; Dissertations, Academic -- South Africa.; Public administration.; Municipal government -- South Africa.; Job satisfaction.